The use of English idiomatic expressions by Uzbek EFL learners and strategies to improve idiom comprehension - Kholmurodov , Davron To‘lqin o‘g‘li; Mukhamedova , Nigora Abdulkhayevna (The Lingua Spectrum, 2026)
The use of English idiomatic idioms by Uzbek learners of English as a foreign language (EFL) is examined in this article, along with practical methods for improving understanding. Gaining near-native fluency requires grasping idioms, which are the cultural and linguistic core of a language. However, because of their cultural subtleties and non-literal interpretations, idioms can be quite difficult for Uzbek learners. The main goal of this study is to identify the particular challenges that students encounter and to provide instructional frameworks that help them learn these complicated expressions more effectively. The study examines typical challenges, including insufficient exposure to real-world language contexts and first-language (L1) interference, in which students attempt literal translations from Uzbek. The article offers a number of cutting-edge teaching techniques to overcome these problems, such as the cognitive linguistic method, which emphasizes the mental analogies behind idioms. To go beyond rote memorization, the use of digital tools, visual aids, and contextual learning is also considered. The results imply that learners have a more profound and long-lasting comprehension of idioms when they are taught through their historical roots and cultural settings. Teachers may assist students in bridging the gap between classroom knowledge and real-world communication by including genuine materials like podcasts and films into the curriculum. For EFL teachers in Uzbekistan looking to improve their methods and raise their students’ communicative proficiency, this study offers insightful information.